2023
DOI: 10.1039/d3cc00499f
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective transformations of 5-hydroxymethylfurfural via catalytic asymmetric 1,3-dipolar cycloaddition of azomethine ylides

Abstract: A copper catalyzed highly diastereo and enantioselective 1,3-dipolar cycloaddition for the preparation of furanyl-pyrrolicines from HMF is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…On the contrary, several research groups have reported different protocols for the dehydrogenative oxidation from pyrrolidines to pyrroles . Thus, in connection with our previous work in 1,3-dipolar cycloaddition and pyrrole synthesis, we envisaged that a metal-catalyzed asymmetric cycloaddition of azomethine ylides and subsequent oxidation of the resulting pyrrolidine could provide an expeditious route to a new class of axially chiral C2-aryl pyrroles, via a central-to-axial chirality transfer strategy (Scheme ). Nonetheless, to achieve this objective, two main issues had to be addressed: (a) the development of a robust asymmetric 1,3-dipolar cycloaddition leading to the preparation of highly enantioenriched pyrrolidines decorated with suitable groups around the C–C axis to avoid free rotation in the final pyrrole core and (b) the achievement of a mild pyrrolidine to pyrrole oxidation process that would allow the efficient central-to-axial chirality transfer.…”
mentioning
confidence: 98%
“…On the contrary, several research groups have reported different protocols for the dehydrogenative oxidation from pyrrolidines to pyrroles . Thus, in connection with our previous work in 1,3-dipolar cycloaddition and pyrrole synthesis, we envisaged that a metal-catalyzed asymmetric cycloaddition of azomethine ylides and subsequent oxidation of the resulting pyrrolidine could provide an expeditious route to a new class of axially chiral C2-aryl pyrroles, via a central-to-axial chirality transfer strategy (Scheme ). Nonetheless, to achieve this objective, two main issues had to be addressed: (a) the development of a robust asymmetric 1,3-dipolar cycloaddition leading to the preparation of highly enantioenriched pyrrolidines decorated with suitable groups around the C–C axis to avoid free rotation in the final pyrrole core and (b) the achievement of a mild pyrrolidine to pyrrole oxidation process that would allow the efficient central-to-axial chirality transfer.…”
mentioning
confidence: 98%